An optimized voxel-based morphometric study of gray matter changes in patients with left-sided and right-sided mesial temporal lobe epilepsy and hippocampal sclerosis (MTLE/HS) - Pail, Martin; Brázdil, Milan; Mareček, Radek; Mikl, Michal (Epilepsia, 2010)
PURPOSE: To determine whether changes in gray matter volume (GMV) differ according to the affected side in mesial temporal lobe epilepsy/hippocampal sclerosis (MTLE/HS) syndrome, and moreover to test the hypothesis of more pronounced structural changes in right-sided MTLE/HS. This hypothesis (especially that the contralateral thalamus is more affected in right-sided MTLE/HS) arose from the results of our recent study, wherein more expressed structural and functional changes were observed in a small sample of patients with right-sided MTLE/HS (Brázdil et al., 2009). METHODS: Twenty patients with left-sided and 20 with right-sided MTLE/HS and 40 sex- and age-matched healthy controls were included in the study. Voxel-based morphometry (VBM) with a modulation step was applied to magnetic resonance imaging (MRI) brain images. Statistical parametric maps were used to compare structural changes between patients and controls separately for the left- and right-sided MTLE/HS subgroups. We also compared the local GMV of the brain structures (insula and thalamus) between the subgroups of patients. RESULTS: In the subgroup with right-sided MTLE/HS, a reduction of GMV was detected in the mesiotemporal structures and the ipsilateral thalamus (as in left-sided MTLE/HS), but also notably in the ipsilateral insula and contralateral thalamus. A statistical analysis revealed a significantly more extensive reduction of GMV in the ipsilateral/contralateral insula and the contralateral thalamus in the subgroup with right-sided compared to left-sided MTLE/HS. CONCLUSION: We found asymmetrical morphologic changes in patients with left- and right-sided MTLE/HS syndrome (more pronounced in right-sided MTLE/HS). These differences could be theoretically explained by different neuronal networks and pathophysiologic changes in temporolimbic structures.
Keywords: Imaging, Three-Dimensional; referenční hodnoty; Magnetic Resonance Imaging; velikost orgánu; magnetická rezonanční tomografie; Humans; Dominance, Cerebral; lidé středního věku; mapování mozku; Atrophy; Parahippocampal Gyrus; epilepsie temporálního laloku; Thalamus; Female; mladý dospělý; dospělí; Temporal Lobe; spánkový lalok; Hippocampus; lidé; hipokampus; počítačové zpracování obrazu; Image Processing, Computer-Assisted; gyrus parahippocampalis; atrofie; thalamus; amygdala; Adult; mozkový kmen; Brain Mapping; dominance mozková; ženské pohlaví; Male; Amygdala; Middle Aged; Epilepsy, Temporal Lobe; skleróza; Young Adult; Brain Stem; Reference Values; zobrazování trojrozměrné; Organ Size; mužské pohlaví; Sclerosis